Малая наука с большими проблемами институционализации. Размышляя об истории литовской этнологии - Шакнис, Ж. (Матеріали до української етнології, 2011)
Статья посвящена истории институционализации этнологии Литвы. В ней делается вывод, что, несмотря на связи этнологии с различными научными дисциплинами и на характерное для нашего времени, постоянное изменение границ наук, ситуация, в которой находится этнология, остаётся неопределенной, и проблема институционализации представляет собой угрозу для дальнейшего существования этнологии как науки. The article deals with the history of the institutionalization of Lithuanian ethnology. The article concludes that, although over the last few decades ethnology has legally become a science independent from history, despite the new possibilities and achievements, it has remained the «little science» with big institutionalisation problems. Notwithstanding the relations of ethnology with various disciplines and the rapidly changing scientific range that agrees with the present situation, the undefined situation of the science and the problems of its institutionalisation endanger its survival.